Low‐Energy (<200 eV) Electron Acceleration by ULF Waves in the Plasmaspheric Boundary Layer: Van Allen Probes Observation. Issue 10 (13th October 2017) - Ren, Jie; Zong, Q.‐G.; Miyoshi, Y.; Zhou, X. Z.; Wang, Y. F.; Rankin, R.; Yue, C.; Spence, H. E.; Funsten, H. O.; Wygant, J. R.; Kletzing, C. A.
Abstract: We report observational evidence of cold plasmaspheric electron (<200 eV) acceleration by ultralow frequency (ULF) waves in the plasmaspheric boundary layer on 10 September 2015. Strongly enhanced cold electron fluxes in the energy spectrogram were observed along with second harmonic mode waves with a period of about 1 min which lasted several hours during two consecutive Van Allen Probe B orbits. Cold electron (<200 eV) and energetic proton (10–20 keV) bidirectional pitch angle signatures observed during the event are suggestive of the drift‐bounce resonance mechanism. The correlation between enhanced energy fluxes and ULF waves leads to the conclusions that plasmaspheric dynamics is strongly affected by ULF waves. Van Allen Probe A and B, GOES 13, GOES 15, and MMS 1 observations suggest that ULF waves in the event were strongest on the duskside magnetosphere. Measurements from MMS 1 contain no evidence of an external wave source during the period when ULF waves and injected energetic protons with a bump‐on‐tail distribution were detected by Van Allen Probe B. This suggests that the observed ULF waves were probably excited by a localized drift‐bounce resonant instability, with the free energy supplied by substorm‐injected energetic protons. The observations by Van Allen Probe B suggest that energy transfer between particle species in different energy ranges can take place through the action of ULF waves, demonstrating the important role of these waves in the dynamical processes of the inner magnetosphere. Key Points: We report observational evidence of cold plasmaspheric electron acceleration by ULF waves in the plasmasphere boundary layer Plasmaspheric dynamics can be strongly affected by ULF waves through drift‐bounce resonance between cold electrons and ULF waves Energy transfer between particle species in different energy range can take place through the action of ULF waves